The icy1 Gene from Saccharomyces Cerevisiae Affects Nitrogen Consumption During Alcoholic Fermentation - Contreras-Opazo, A; Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V (Electronic Journal of Biotechnology, 2014)
Background: Saccharomyces cerevisiae is the main microorganism responsible for alcoholic fermentation. In this process, the consumption of nitrogen is of great importance since it is found in limiting quantities and its deficiency produces sluggish and/or stuck fermentations generating large economic losses in the wine-making industry. In a previous work we compared the transcriptional profiles between genetically related strains with differences in nitrogen consumption, detecting genes with differential expression that could be associated to the differences in the levels of nitrogen consumed. One of the genes identified was ICY1. With the aim of confirming this observation, in the present work we evaluated the consumption of ammonium during the fermentation of strains that have deleted or overexpressed this gene.Results: Our results confirm the effect of ICY1 on nitrogen uptake by evaluating its expression in wine yeasts during the first stages of fermentation under low (MS60) and normal (MS300) assimilable nitrogen. Our results show that the mRNA levels of ICY1 diminish when the amount of assimilable nitrogen is low. Furthermore, we constructed strains derived from the industrial strain EC1118 as a null mutant in this gene as well as one that overexpressed it.Conclusions: Our results suggest that the expression of ICY1 is regulated by theamount of nitrogen available in the must and it is involved in the consumption of ammonium, given the increase in the consumption of this nitrogen source observed in the null mutant strain. © 2014 Pontificia Universidad Católica de Valparaíso. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Enological traits; Gene expression; Wine fermentation; Wine yeast